1987
DOI: 10.1063/1.866328
|View full text |Cite
|
Sign up to set email alerts
|

The solution of the plasma equation in plane parallel geometry with a Maxwellian source

Abstract: The plasma equation for a warm collisionless plasma with a Maxwellian particle source is solved in plane parallel geometry. The generalized Bohm criterion is used to identify the plasma–sheath boundary. This kinetic treatment, in common with fluid and cold-ion kinetic models, results in an infinite electric field at the sheath edge. This is in sharp contrast to results from a previous warm-ion kinetic model, by Emmert et al. [Phys. Fluids 23, 803 (1980)], which gave a finite electric field at the sheath edge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 9 publications
0
85
0
Order By: Relevance
“…This particular comparison of exact potential profiles with finite e's was obtained here for the Maxwellian distributed ion source with temperature T n =T e ¼ 10 via a highly reliable numerical computational method developed by Kos et al 6,20 for dealing with the complete T&L collisionless discharge model as well as with its special case of quasineutral plasma known as Bissell and Johnson (B&J) model. 2,3 This method has proved as superior to others known by us in obtaining results with an extremely high resolution and at the same time being applicable to a wide (practically unlimited) range of ion source temperatures.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This particular comparison of exact potential profiles with finite e's was obtained here for the Maxwellian distributed ion source with temperature T n =T e ¼ 10 via a highly reliable numerical computational method developed by Kos et al 6,20 for dealing with the complete T&L collisionless discharge model as well as with its special case of quasineutral plasma known as Bissell and Johnson (B&J) model. 2,3 This method has proved as superior to others known by us in obtaining results with an extremely high resolution and at the same time being applicable to a wide (practically unlimited) range of ion source temperatures.…”
Section: Introductionmentioning
confidence: 89%
“…Achieving this goal requires an exhaustive analysis consisting of many consecutive steps, e.g., rescaling the potential profile appropriately in the so-called "intermediate scale," in whose a) representation the potential profiles are nearly independent on discharge parameter e. Riemann has recently 4 summarized the "state of the art" of plasma-sheath analysis showing that there are three models that should be distinguished, namely (1) fluid model, (2) kinetic model with ions generated with zero initial velocity (so-called "cold" or "singular" ion source), and (3) kinetic model with ions generated with a finite initial velocity (the so-called "warm" or "regular" ion source). While proper analysis was performed within fluid approximation and the kinetic model with "cold" ion sources, Riemann states that "the structure of the plasma-sheath transition for models with hot ion source was never analyzed!"…”
Section: Introductionmentioning
confidence: 99%
“…The complete plasma-sheath equation was solved numerically. Solving the plasma equation for a Maxwellian particle source S i ( , ) ξ η ∼ exp( ) − η , Bissel et al [5,6] showed that the final result is essentially sensitive to the choice of the source function.…”
Section: Introductionmentioning
confidence: 99%
“…The inodilisd inotlcl of TJissd and J o l i i i~o~i [7] 1i;rs it "aornial" sourcc. A surprising contradiction between kinetic arid hydrodynamic analysis occurs in lhe case of supersonic ion flow.…”
Section: I1 Bohm Criterion and Sheath Edge Field Singularitymentioning
confidence: 99%